Impact of patient's habitus on image quality and quantitative metrics in 18F-FDG PET/CT images. (May 2023) - Zorz, Alessandra; D'Alessio, Andrea; Guida, Federica; Ramadan, Rehema Masaka; Richetta, Elisa; Cuppari, Lea; Pellerito, Riccardo; Sacchetti, Gian Mauro; Brambilla, Marco; Paiusco, Marta; Stasi, Michele; Matheoud, Roberta
Highlights: SUVmax and SULmax variation increases with PET scan duration. SUVmax values are significantly higher in high BMI patients. SULmax values are independent of patient's BMI. Noise is higher in high BMI patients and decreases when increasing acquisition time. Use of SUL is recommended for improve lesion quantification accuracy. Abstract: Purpose: To study how the quantitative parameters of 18F-FDG PET imaging change with the emission scan duration (ESD) and the body-mass-index (BMI) in phantom and patients on a time-of-flight (TOF)-PET/CT system. Methods: The image-quality phantom with (b-NEMA-IQ, BMI = 29.2 kg/m 2 ) and without (NEMA-IEC, BMI = 21.4 kg/m 2 ) a 'belt' of water-bags was filled with 18F-FDG activities to obtain nominal standardized uptake values (SUV) of 19, 8 and 5. Patients with BMI ≤ 25 kg/m 2 (L-BMI) and BMI > 25 kg/m 2 (H-BMI) were enrolled in this study. Phantom and patients underwent list-mode PET acquisition at 120 s/bed-position. Images reconstructed with clinical protocol and different ESD (120, 90, 75, 60, 45, 30 s) were analysed for comparison of maximum SUV (SUVmax ), maximum standardized uptake value lean-body-mass corrected (SULmax ) and noise. Results: 79 oncologic patients (45 L-BMI, 44 H-BMI) were analysed. From 90 s to 30 s, an increasing variation of SUVmax and SULmax with respect to the reference 120 s time was observed, from 18% to 60% and from 16% to 37% for phantom and patients, respectively. SUVmax values were significantly higher (+50%) in b-NEMA-IQ than NEMA-IQ phantom and in H-BMI (+33%) than L-BMI patients. No significant difference was found in SULmax for the two BMI categories in both phantom and patients. CV values decreased when increasing ESD, being higher in H-BMI patients (0.13–0.25) and b-NEMA-IQ phantom (0.15–0.28) than in L-BMI patients (0.11–0.21) and NEMA-IQ phantom (0.11–0.20). Conclusions: Reduction of ESD may severely impact on the variations of SUVmax and SULmax in 18F-FDG PET/CT imaging. This study confirms recommendations of using SUL for lesion uptake quantification, being unaffected by BMI variation.